CULTURAL RELATIONS OF UZBEKISTAN AND TURKMENISTAN ON THE PAGES OF “XALQ SO‘ZI” NEWSPAPER (2001-2019) - Subkhonova Niso Akhmadovna; O.A. Klichev (Journal Park Publishing, 2023)
This article analyzes the coverage of the cultural friendship relations between the Republics of Uzbekistan and Turkmenistan during the years 2001-2019 in the pages of the “Xalq so‘zi” newspaper. Also, the article describes the place and role of “Xalq so‘zi” newspaper as an important source in commenting on the fact that the cultural relations established over the years are carried out on the basis of loyalty to traditions between the two peoples.
Keywords: cultural center, conference, forum, festival, dream ensemble, council, “Ashkhabad” recreation park, “Eastern songs”.